An embedding traid-bit method to improve the performance of Arabic text steganography - Thabit, Reema Ahmed Abdalla (2016)
The enormous development in the utilization of the Internet has driven by continuous improvements in the region of security. The enhanced security techniques are applied to save the intellectual property. There are numerous sorts of security mechanisms. Steganography is the art and science of concealing secret information inside a cover media without drawing any suspicion to the eavesdropper so that the secret information can only be detected by its proposed recipient. This is done along with the other steganography methods such as image, audio, video, various text steganography methods that are being presented. The text is ideal for steganography due to its ubiquity. There are many steganography methods used several languages such as English, Chines and Arabic language to embed the hidden message in the cover text. Kashida, shifting point and sharp_edges are Arabic steganography methods with high capacity. However, kashida, shifting point and sharp_edges techniques have lack of capability to embed the hidden message into the cover text. This study proposed new method called Traid-bit method by integrating three several types of methods such us kashida, shifting point and sharp_edges to evaluate the proposed method in improving the performance of embedding process. The study presents the process design of proposed method including the algorithms and the system design. The study found that the evaluation of the proposed method provides good knowledge to steganographer to improve the performance of embedding process when the Arabic text steganography method is developed.